PENGARUH KOMPETENSI SPIRITUAL DAN PENGGUNAAN MEDIA PEMBELAJARAN DIGITAL TERHADAP MINAT BELAJAR PENDIDIKAN AGAMA KRISTEN SISWA SMPN 4 SIAK HULU TAHUN PEMBELAJARAN 2025/2026 - Rahmat Simbolon; Hisardo Sitorus; Baginda Sitompul (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The purpose of this study was to determine 1) the effect of spiritual competence on the interest in learning Christian Religious Education of students at SMPN 4 Siak Hulu in the 2025/2026 academic year; 2) the effect of the use of digital learning media on the interest in learning Christian Religious Education of students at SMPN 4 Siak Hulu in the 2025/2026 academic year; and 3) the effect of spiritual competence and the use of digital learning media together on the interest in learning Christian Religious Education of students at SMPN 4 Siak Hulu in the 2025/2026 academic year. The method used in this study is a descriptive quantitative method. The population is all students at SMPN 4 Siak Hulu who are Protestant Christians totaling 431 people and a sample of 65 people is determined, which is 15% of the total population. The instrument trial was conducted on 31 students of SMPN 4 Siak Hulu so that it is known that all research instruments are declared valid and reliable because they have met the criteria for validity and reliability values. Data were collected with a closed questionnaire of 60 items. The results of the data analysis show that: 1) the Fcount value > Ftable is 20.301 > 3.15, thus it is known that there is a positive and significant influence of spiritual competence on the interest in learning Christian Religious Education of students of SMPN 4 Siak Hulu in the 2025/2026 Academic Year. The influence is 24.4%; 2) the Fcount value > Ftable is 16.105 > 3.15, thus it is known that there is a positive and significant influence of the use of digital learning media on the interest in learning Christian Religious Education of students of SMPN 4 Siak Hulu in the 2025/2026 Academic Year. The influence is 20.4%; and 3) the Fcount value > Ftable is 13.597 > 3.15, thus it is known that there is a positive and significant influence of spiritual competence and the use of digital learning media together on the interest in learning Christian Religious Education of students of SMPN 4 Siak Hulu in the 2025/2026 Academic Year. The influence is 30.5%, thus Ha is accepted and H0 is rejected.